OPEN SOURCE INTELLIGENCE: AN OVERVIEW OF TODAY’S OPERATIONAL CHALLENGES AND HUMAN RIGHTS AFFECTED AS A CONSEQUENCE - Ainara BORDES PEREZ (Romanian Intelligence Studies Review, 2023)
This article analyses those operational challenges and their subsequent impacts on human rights. It does so by doing a comprehensive literature review on the topic through academic articles, national and international institutional reports, and newspaper articles. The study focuses on concrete problematic activities involving the creation and use of current OSINT products and describes examples that are not limited to one jurisdiction. Structuring both the OSINT operational challenges and their subsequent impacts on human rights is the novelty of this article. While some academics have addressed several of those challenges affecting advanced mining technologies overall, addressing the operational challenges and their impacts from a single focal point – OSINT, is novel. Addressing them in a structured manner is a necessary first step to carve up the landscape for a potential subsequent legislative evaluation of how to address those operational challenges and their impacts on human rights.